Safety evaluation of a buffer used in the lyophilization of canine platelets: type I hypersensitivity reaction in dogs caused by bovine serum albumin - Choi, Hee-Jae; Kim, Mu-Young; Han, Hyun-Jung (Frontiers in Veterinary Science, 2024)
The present study was designed to evaluate the safety of substances generally used in the preparation of lyophilized platelet products (LPPs) because the possibility of an immune response to bovine serum albumin (BSA) was considered high when using previously described technology. Methods: An intradermal skin test, followed by a drug provocation test, was conducted to observe adverse events and identify the substances responsible for an immune response. Five male beagles (2 years old) weighing 12-14 kg were used. The dogs were clinically healthy and had no history of medication use. An intradermal skin test was conducted with each substance [i.e., 4-(2hydroxyethyl)-1-piperazine ethanesulfonic acid, sodium chloride, potassium chloride, sodium bicarbonate, theophylline, trehalose, and BSA] used in the conventional freeze-dry method. Results: In the intradermal skin test, three dogs tested positive at the BSA injection site and showed clinical signs after the intradermal injection, including nausea and vomiting. For the drug provocation test, all dogs received two intravenous injections of an LPP buffer solution. The initial injection was devoid of BSA, whereas the subsequent injection contained BSA. The three dogs that had reacted to BSA in 삭제함: 3166 32 삭제함: ),삭제함: , the intradermal skin test exhibited adverse events such as lethargy, vomiting, and nausea immediately after intravenous injection of the LPP buffer containing BSA. All dogs recovered uneventfully after symptomatic treatment in both tests. Discussion: The high incidence and severity of type I hypersensitivity reactions observed in this study suggested that BSA is unsuitable as a component of canine LPP.